PENTINGNYA TINDAK TUTUR KESANTUNAN SISWA KEPADA GURU DALAM PROSES BELAJAR MENGAJAR - Widyahening, Ch Evy Tri (UNIVERSITAS SLAMET RIYADI, 2011)
Abstract The suavity of speaking talks about the decent of linguistic and the usage. A man is told that he has a decent speaking if he fulfills some suavity maxims. In social life, the decent speaking has the important role in communicating. Suavity of speech act must be performed by all people to take care of interaction quality in the job world and every activity in the social world. Suavity of speech act also must be performed by the students when they are in school and is claiming science. A student, whom can talk decent, gets the first education to talk decent from its family. All stand and behavior of his or her parents is very influential to develop his or her real life, therefore his or her parent’s stand and behavior will be observed by him or her and it will affect his or her stand and behavior. In school, the representative of formal education which must in goes through by all of students, there is interaction between an educator (a teacher) and a student as a subject learner. Here, language which is used as a means of communications so central important role to take care of quality of interaction with suavity speaking. Keywords: Suavity Speaking, speech act, linguistics, maxims.